Effects of video-assisted diabetic foot exercises on self-efficacy and glycemic control in adults with type 2 diabetes mellitus - Yokki Dio Sandhika; Sri Maryuni; Nova Nurwinda Sari (JOURNAL OF Mental Health Concerns, 2026)
Background: Type 2 diabetes mellitus (DM) is a chronic disease characterized by elevated blood sugar levels due to insulin resistance. DM management involves more than just pharmacological therapy, but also requires non-pharmacological interventions such as physical activity. Video-assisted DM foot exercises are a simple form of exercise that can be performed independently by DM sufferers. Purpose: To determine the effect of video-assisted DM foot exercises on random blood sugar levels in type 2 DM sufferers. Method: A pre-experimental design with a one-group pre-test–post-test approach. The sample consisted of 25 type 2 diabetes patients selected using a purposive sampling technique. The intervention, which included video-based DM foot exercises, was administered according to established procedures. Random blood sugar levels were measured before and after the intervention. Data were analyzed using a paired t-test. Results: The average random blood sugar level before the intervention (pre-test) was 223.88 mg/dL and after the intervention (post-test) it decreased to 185.40 mg/dL. The results of the Paired t-test showed a t value = 4.811 with a p-value = 0.000 (p < 0.05), which indicates a significant effect of DM foot exercise with video media on reducing random blood sugar levels. Conclusion: DM foot exercises using video media have a significant effect on reducing random blood sugar levels in type 2 DM patients. It is recommended that DM foot exercises can be implemented routinely as a non-pharmacological intervention in primary health care. Keywords: DM Foot Exercises; Random Blood Sugar Levels; Type 2 Diabetes Mellitus; Video Media.